A dendrite-suppressed and utilization-improved metallic Li anode enabled by lithiophilic nano-Pb decoration on carbon cloth. Issue 15 (15th March 2022) - Du, Peng; Yuan, Chenbo; Cui, Xiaoyu; Zhang, Kaifu; Yu, Yu; Ren, Xiaodi; Zhan, Xiaowen; Gao, Shan
Abstract : A dendrite-suppressed, utilization-improved metallic Li anode was fabricated via a record-fast (1.0 s) infusion of molten Li into Pb-decorated carbon cloth at 250 °C. Abstract : The commercialization of Li metal anodes has been long hindered by uncontrolled dendrite growth, infinite volume expansion and poor Li metal utilization. Herein, we achieve a uniform nano-Pb decoration on carbon cloth (Pb@CC) by exploiting the thermal decomposition process of lead acetate trihydrate monitored by in situ Raman spectroscopy. 3D hosted Li anodes are fabricated via a record-fast infusion (1.0 s) of accurate weight-controlled molten Li into the highly lithiophilic Pb@CC host at a considerably low temperature of 250 °C. At an optimal Li loading of 10 mg, the Pb nanoparticles guide the uniform distribution of Li sites over the robust yet porous electron-conducting carbon network, which not only directs and confines Li nucleation and growth, but accommodates volume changes during repeated Li stripping/plating processes. The resulting Li electrodes afford an ultralong cycle life of 4648 h at low overpotentials of <50 mV under 1 mA cm −2 /1 mA h cm −2 symmetric-cell cycling, which is among the best records ever reported in the literature. The corresponding LiFePO4 and LiNi0.8 Co0.1 Mn0.1 O2 full cells deliver significantly higher cycling and rate performances than those with Li foils. Furthermore, the effect of Li utilization is explored in Li‖LiFePO4 full cells, with the best cyclability achieved at a low N/P ratio of 63.28. The present findings stretch the practical feasibility of wetting-assisted molten Li infusion in mitigating dendrite growth and improving Li utilization towards long-cycling high-energy-density Li metal batteries.